Bromide: the good, the bad, and the ugly of the oldest antiseizure medication - Gouveia, Diogo; Mandigers, Paul; Cherubini, Giunio Bruto (Frontiers in Veterinary Science, 2024)
Bromide is the first effective antiseizure medication used in human medicine since the XIX century. Initially met with scepticism, bromide quickly gained enthusiasm within the medical field until being largely replaced by newer antiseizure medications with significantly fewer adverse effects in people. In veterinary medicine, bromide continues to be used in the management of epileptic patients for over 30 years, yet adverse effects can impact owners and patients alike. We sought to provide the general practitioner and veterinary neurologist with insightful information on both the positive and negative attributes of bromide, explore factors that may influence its desirability as an antiseizure medication in specific veterinary cases and elucidate its current role in modern epilepsy treatment for veterinary patients. It's also our endeavour to discuss the current use as an alternative or add-on with other known antiseizure medications and potential future studies that might enhance our understanding and use of this medication.1. Introduction Epilepsy is the term used to describe a brain disease that leads to a persistent predisposition for the generation of epileptic seizures, with this term being applied to patients that experience at least two unprovoked epileptic seizures separated from more than 24 hours (Berendt et al., 2015). A systematic review and metanalysis by Fiest et al. ( 2017) identified a point prevalence of active epilepsy of 6.38 per 1000 people. In canine patients, epilepsy was found to be the most prevalent chronic neurological disorder (Ukai et al., 2021;Grady et al., 2023). Although the exact point prevalence is not known, this was estimated to be between 0.6 to 0.75% in the general dog population (Berendt et al., 2015). Epilepsy can also occur in cats. O'Neil et al. (2020) reported epilepsy with a one-year period prevalence of 0.04% for patients presenting to primary veterinary care practices in the United Kingdom. Idiopathic epilepsy (IE), which can be further subclassified into genetic epilepsy, suspected genetic epilepsy or IE of unknown cause, is the most common cause responsible for seizures in